Impact of chemotherapy during pregnancy on fetal growth. (30th December 2022) - Maggen, Charlotte; Wolters, Vera E. R. A.; Van Calsteren, Kristel; Cardonick, Elyce; Laenen, Annouschka; Heimovaara, Joosje H.; Mhallem Gziri, Mina; Fruscio, Robert; Duvekot, Johannes J.; Painter, Rebecca C.; Masturzo, Bianca; Shmakov, Roman G.; et al.
Abstract: Background: Chemotherapy crosses the placenta, however, it remains unclear to what extent it affects fetal growth. The current literature suggests up to 21% of the offspring of women receiving chemotherapy are small for gestational age (SGA, birth weight <10th percentile). Limiting research to birth weights only might misjudge fetal growth restriction (FGR) in this high-risk population with multiple risk factors for impaired fetal growth. Moreover, the role of the duration of chemotherapy and gestational age at initiation of chemotherapy in fetal growth is yet poorly understood. Objective: This retrospective cohort study evaluates fetal growth and neonatal birthweights in pregnant women receiving chemotherapy. Study design: All pregnant patients, registered by the International Network of Cancer, Infertility and Pregnancy (INCIP), treated with chemotherapy with at least two ultrasounds reporting on fetal growth, were eligible for this study. Duration and gestational age at initiation of chemotherapy were our major determinants, followed by cancer type and stage, maternal characteristics (parity, BMI, ethnicity hypertension, and diabetes) and individual cytotoxic agents (anthracycline, taxanes, and platinum). Fetal growth outcomes were described using the following mutually exclusive groups (1) FGR, based on a Delphi consensus (2016); (2) "low risk SGA" (birth weight below the 10th percentile), but an estimated growth above the 10th percentile; (3) "fetal growth disturbance", which did not meet all FGR criteria; (4) "non-FGR". Obstetric and oncological characteristics were compared between the growth impaired groups and non-FGR group. We calculated estimated fetal weight (EFW) according to Hadlock's formula (1991) and birth weight percentile according to Nicolaides (2018). We used univariable and multivariable regression, and linear mixed effect models to investigate the effect of duration and gestational age at initiation of chemotherapy on birth weight, and fetal growth, respectively. Results: We included 201 patients, diagnosed with cancer between March 2000 and March 2020. Most patients were diagnosed with breast cancer ( n = 132, 66%). Regimens included anthracyclines ( n = 121, 60%), (anthracyclines and) taxanes ( n = 45, 22%) and platinum ( n = 35, 17%). Fetal growth abnormalities were detected in 75 pregnancies: 43 (21%) FGR, 10 (5%) low risk SGA and 22 (8.5%) fetal growth disturbance. Chemotherapy prior to 20 weeks of gestation (47% vs. 25%, p = .04) and poor maternal gestational weight gain (median percentile 15 (range 0–97) vs. 8 (0–84), p = .03) were more frequent in the FGR group compared to the non-FGR group, whereas no difference was seen for specific chemotherapy or cancer types. Univariable regression identified gestational weight gain, hypertension, systemic disease, parity, neonatal sex and maternal BMI as confounders for birth weight percentiles. Multivariable regression revealed that each additional week of chemotherapy was associated with lower birth weight percentiles (–1.06; 95%CI −2.01; −0.04; p = .04), and that later initiation of chemotherapy was associated with an increase in birth weight percentile (1.10 per week; 95%CI 0.26; 1.95; p = .01). Each additional week of chemotherapy was associated with lower EFW and abdominal circumference (AC) percentiles (–1.77; 95%CI −2.21; −1.34, p < .001; −1.64; 95%CI −1.96; –1.32, p < .001, respectively). Conclusions: This study demonstrates that FGR is common after chemotherapy in pregnancy, and that the duration of chemotherapy has a negative impact. Sonographic follow-up of fetal growth and well-being is recommended.